Pelatihan CorelDraw Untuk Desain Grafis Bagi Siswa SMA Negeri I Grujugan - Taufiq Timur Warisaji; Ulya Anisatur Rosyidah; Ari Eko Wardoyo (Jurnal Pengabdian Masyarakat Manage, 2023)
The media for transmitting human information in daily life are mainly language and pictures, and scientific and statistical research shows that about 75% of the information humans get from the outside world comes from the visual system, which is obtained from pictures. This shows that image information plays a very important role in conveying information. Later, as technology developed, computers gradually became popular, and people began to use computers to process images. Graphic design is everywhere in modern life, including in packaging, advertisements, books and websites, among many others. Designs are often difficult to create, as they must convey information clearly while also serving an aesthetic goal. Designers now also have to create designs for a variety of display sizes, from mobile phones to posters, and often have to retarget designs of various sizes. Also, many designs are created by inexperienced users with little training in graphic design. Automated tools for creating, adapting, and improving graphic designs can be of great help to designers, and in particular, novice users. Grujugan High School sets graduate targets as educational outcome standards, including: 1) Strong Aqidah, 2) Karimah Morals 3) High academic achievement, 3) Strong leadership, 4) Excellent physical condition, 5) Disciplined, 6) National, global and insightful Islamic, 7) have the basics of entrepreneurial spirit, 8) have basic skills for work, and 9) be independent and have a social spirit. To achieve these output targets in order to achieve the school's vision, the school establishes a school curriculum that combines the National curriculum, namely the Education Unit Level Curriculum (KTSP) and the school's distinctive curriculum. The expected outcome in this community service activity is that each student has adequate knowledge and skills regarding graphic design using CorelDraw as a support that relates to the world of graphic design. After each student has adequate basic knowledge and design skills with CorelDraw, the follow-up to this activity is the practice of making poster designs using CorelDraw. This community service activity went smoothly and according to plan, the students gained additional insight and additional skills about the world of graphics and the use of Corel Draw software as a medium to help create simple graphic designs in the form of posters and banners